PHENOLIC PROFILE OF Centaurea aegyptiaca L. GROWING IN EGYPT AND ITS CYTOTOXIC AND ANTIVIRAL ACTIVITIES - Bakr, Riham Omar; Mohamed, Shaza Abd El Halim; Ayoub, Nahla (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Centaurea aegyptiaca L (Asteraceae), is one of the most attractive plants growing wildly in Sinai, and is not wellinvestigated for its phytochemical constituents. This study represents the first in-depth characterization of the phenolic profile of theaerial parts of C. aegyptiaca methanolic extract utilizing liquid chromatography (LC) combined with electrospray ionization (ESI)tandem mass spectrometry (MS/MS).Material and Methods: Phenolic profile was researched utilizing LC-HRESI-MS-MS. Assessment of cytotoxic activity against fourhuman cancer cell lines (Hep-G2; hepatocellular carcinoma cells, MCF-7; breast adenocarcinoma cells, and HCT-116; coloncarcinoma and HELA; cervical carcinoma cells) was performed using 3-[4,5-dimethylthiazole-2-yl]-2,5-diphenyltetrazoliumbromide (MTT) assay. Antiviral activity was surveyed utilizing cytopathic effect inhibition assay.Results: A total of sixty-one compounds were tentatively distinguished (twenty-one phenolic acids and their derivatives, thirty-oneflavonols and nine flavones) in the negative and positive modes. Centaurea aegyptiaca demonstrated outstanding results againstHep-G2, MCF-7, HCT-116 and HELA cell lines with IC50 of 12.1, 30.9, 11.7 and 19.5 μg/mL respectively compared anddoxorubicin as a reference drug. Weak antiviral activity was seen against hepatitis A virus (HAV) and no impact against herpessimplex virus type 1 (HSV 1).Conclusion: This study provides a better understanding of the chemistry of C. aegyptiaca that announces itself as a promisingcytotoxic agent.